2012
DOI: 10.1177/1358863x12463491
|View full text |Cite
|
Sign up to set email alerts
|

A validated biomarker panel to identify peripheral artery disease

Abstract: Current guidelines recommend obtaining an ankle-brachial index (ABI) to screen for peripheral artery disease (PAD) in subjects at risk. Previous work demonstrated that a combination of β(2)-microglobulin, cystatin C, high-sensitivity C-reactive protein and glucose was associated with PAD. This study evaluated the ability of these biomarkers combined with clinical parameters to predict PAD in at-risk subjects. This study enrolled 1025 subjects from 99 primary care clinics who were smokers and/or diabetics ≥ 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Elevated markers of inflammation, including high-sensitivity C-reactive protein, interleukin-6, fibrinogen, soluble vascular cell adhesion molecule-1, soluble intercellular adhesion molecule-1, asymmetric dimethylarginine, b-2 macroglobulin, and cystatin C are novel risk factors whose clinical utility for predicting PAD onset or progression is not yet clear. [23][24][25][26][27][28][29][30][31][32]…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Elevated markers of inflammation, including high-sensitivity C-reactive protein, interleukin-6, fibrinogen, soluble vascular cell adhesion molecule-1, soluble intercellular adhesion molecule-1, asymmetric dimethylarginine, b-2 macroglobulin, and cystatin C are novel risk factors whose clinical utility for predicting PAD onset or progression is not yet clear. [23][24][25][26][27][28][29][30][31][32]…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…On the other hand, cross-sectional, observational studies utilizing single measurements of β 2 M yielded partially conflicting associations [ 24 ],[ 55 ]. More recently, associations have been reported between β 2 M and survival (all-cause and cardiovascular in NHANES [ 56 ] and ARIC [ 57 ]), cardiovascular events and calcification in CKD [ 25 ], early-onset atherosclerosis in ESRD [ 58 ], stroke [ 59 ], peripheral arterial disease [ 60 63 ], and mortality in patients undergoing coronary angiography. [ 64 ] Although observational, these associations have held against adjustments for known risk factors and the prevailing level of kidney function (as assessed with cystatin-C or eGFR) suggesting that β 2 M elevations may have pathologic significance above and beyond its association with glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that a combination of β-2-microglobulin (B2M), cystatin C, high-sensitivity C-reactive protein (hsCRP) and glucose was associated with PAD [65,66]. Plasma B2M levels and parameters of arterial stiffness such as aortic pulse wave velocity and augmentation index have been reported to be significantly increased in PAD patients [67].…”
Section: Potential Biomarkers For Padmentioning
confidence: 99%
“…Plasma B2M levels and parameters of arterial stiffness such as aortic pulse wave velocity and augmentation index have been reported to be significantly increased in PAD patients [67]. Some studies have shown that combining these circulating markers of inflammation and atherosclerosis with clinical parameters may improve the identification of PAD patients [65,66,71]. A previous nested case-control study reported an increased relative risk of PAD (2.8, 95% CI: 1.3–5.9) for subjects in the highest hsCRP quartile compared with the lowest quartile [89].…”
Section: Potential Biomarkers For Padmentioning
confidence: 99%